A brief history of the formation and activities of the M. Bakhtin Viciebsk circle - Nikonov, Alexander N. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
This article discusses the process of the formation of a cultural phenomenon, which in the scientific community is called the M. Bakhtin Viciebsk circle. The main stages of the biography of the thinker, which are associated with his moving from Nevel to Viciebsk and staying in this city, are considered. The role of P. Medvedev in the creation of this intellectual association is shown. The facts of scientific and pedagogical activity of M. Bakhtin himself and people from the creative environment of Viciebsk, who were in his immediate circle and had a significant influence on his formation as a philosopher, were studied.